2020
DOI: 10.17511/ijmrr.2020.i05.02
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of cisgender and transgender during COVID-19 pandemic

Abstract: Normally every individual wants to lead a free life movement but sometimes could not possible due to external environmental effects. During and after the home quarantine, people are still scared by consistent death and infected news of 2019-nCoV pandemic. Which is why, most of the persons have been feeling insecure and nervous that significantly growing up long term stress. The current study depicts the ongoing mental health condition of Bangladeshi cisgender and transgender individuals caused by SARS-CoV-2 ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Literally, such kind of healthcare faux pas explicitly affected the mental health or life satisfaction of the people in the country, and implicitly declined the trust on healthcare service in the country [2, 3,4]. Therefore, many participants experienced unexpected mental distress in Bangladesh, which is similar to other studies [1,7,14,15]. The current study also found that the life satisfaction was dramatically dropped among Bangladeshi people.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Literally, such kind of healthcare faux pas explicitly affected the mental health or life satisfaction of the people in the country, and implicitly declined the trust on healthcare service in the country [2, 3,4]. Therefore, many participants experienced unexpected mental distress in Bangladesh, which is similar to other studies [1,7,14,15]. The current study also found that the life satisfaction was dramatically dropped among Bangladeshi people.…”
Section: Discussionsupporting
confidence: 80%
“…In Bangladesh, the COVID-19 pandemic has dreadfully hit the healthcare industry [1]. The whole health care system is now broken down to control the SARS-CoV-2 pandemic patient management in the country [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations